Minat Petani dalam Penerapan Pemupukan Berimbang dengan Teknologi Urea Berlapis Asam Humat pada Tanaman Padi Sawah di Kecamatan Rancakalong Sumedang - Tuti Nurhayati; Endang Krisnawati; Nawangwulan Widyastuti (Politeknik Pembangunan Pertanian Bogor, 2020)
Agricultural development requires an active role from an outreach agency that is responsible for facilitating the adoption of agricultural technology innovations by farmers. To realize the development of agriculture it is necessary cooperation between the implementing agencies of agricultural development that are able to interact directly with the farmer well and understand the obstacles that are facing farmers and able to provide a coaching to solve the problem. From the results of the identification done in the field, it can be known that the problem lies in the cultivation activities that do not apply a balanced fertilizing concept, so that the soil is experiencing quality degradation and infertile anymore. The effort can be done is with the application of humic acid use. This assessment is aimed to know the interests of farmers in the application of balanced fertilization, factors affecting interest and strategies to increase the interest of farmers in the application of fertilization balanced with the urea technology Berlapois humic acid on rice cultivation in the district Rancakalong Sumedang District. Based on the results of the analysis is the influence of several factors that are dependent variables, as for the strategy to be done is improving the role of extension and agricultural extension activities.